Health Public Expenditure Review : Zimbabwe - World Bank Group (World Bank, Washington, DC, 2015)
This Public Expenditure Review (PER) for health in Zimbabwe is an analytical report developed by the World Bank Health, Nutrition and Population Task Team working with the World Bank’s Macroeconomics and Fiscal Management Global Practice team, Zimbabwe’s Ministry of Finance and Economic Development (MOFED) and Ministry of Health and Child Care (MOHCC), with input from development partners. The aims of the PER are to provide objective evidence to inform the allocation of resources to enable equitable, efficient, and sustainable health care provision and to highlight questions about health sector performance for policy makers and key stakeholders. The findings also aim to present Zimbabwe’s health sector spending in an international and regional perspective, highlighting key issues for improving health outcomes. The PER is based on analysis of primary and secondary data as well as an extensive review of existing literature. The research was complemented by interviews with key stakeholders, and data collection from major development partners and domestic health funders, including private companies. Micro-level data from household and health facility surveys in May–August 2014 (primarily for the impact evaluation of the Results-Based Financing (RBF) program supported by the World Bank) complemented these scarce data.